2011
DOI: 10.1111/j.1464-410x.2011.10680.x
|View full text |Cite
|
Sign up to set email alerts
|

Varicocoele and saphenofemoral reflux: are they coincidentally related?

Abstract: 8 5 3What ' s known on the subject? and What does the study add? It has been proposed that there is a signifi cant relation between varicocoele and saphenofemoral refl ux.Our results show that there is no statistically signifi cant relation between varicocoele and saphenofemoral refl ux. OBJECTIVE• To determine whether a relation between varicocoele and venous insuffi ciency at the level of the saphenofemoral junction (SFJ) is present. PATIENTS AND METHODS• A total of 100 patients with varicocoele and 50 age-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…18 In contrast to previous studies, Yazici also carried out a prospective age-matched study which found no statistically significant relationship between saphenofemoral insufficiency and varicocele. 10 The authors of the study suggested that this discrepancy could be accounted for by the significantly larger number and the relatively younger varicocele patients included. In recent years, other studies have reported findings consistent with the present study and hypothesized that a systemic vascular insufficiency could explain their findings; however, the exact cause is still unclear.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…18 In contrast to previous studies, Yazici also carried out a prospective age-matched study which found no statistically significant relationship between saphenofemoral insufficiency and varicocele. 10 The authors of the study suggested that this discrepancy could be accounted for by the significantly larger number and the relatively younger varicocele patients included. In recent years, other studies have reported findings consistent with the present study and hypothesized that a systemic vascular insufficiency could explain their findings; however, the exact cause is still unclear.…”
Section: Discussionmentioning
confidence: 98%
“…Five of the seven included case-control studies reported the risk of saphenofemoral insufficiency in the varicocele and control groups. 6,[8][9][10]13 In four studies, saphenofemoral insufficiency was defined as femoral saphenous reflux time greater than 0.5 s. In one remaining study, femoral saphenous reflux was defined as retrograde flow of more than 1 s. Ultimately, 872 cases were included, with 482 cases in the varicocele group and 390 cases in the control group. The pooled analysis indicated that the risk of saphenofemoral insufficiency in the varicocele group was higher than that in the control group (OR: 2.80; 95% CI: 2.03, 3.84; p < 0.00001; Figure 4), and low heterogeneity in the pooled effect estimates was found (p = 0.32; I 2 = 14%; Figure 4).…”
Section: Saphenofemoral Insufficiencymentioning
confidence: 99%
See 1 more Smart Citation